If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=n/2+3
We move all terms to the left:
-6-(n/2+3)=0
We get rid of parentheses
-n/2-3-6=0
We multiply all the terms by the denominator
-n-3*2-6*2=0
We add all the numbers together, and all the variables
-1n-18=0
We move all terms containing n to the left, all other terms to the right
-n=18
n=18/-1
n=-18
| 5x+10+40=12x+8 | | 3/4y+2=1/4y+1/2y | | 137+102+x=94 | | 137+102+x=95 | | 6.2x=5x-9x+14 | | 137+102+x=92 | | 3x-10=4- | | 45m=90 | | 26=13a | | Y+4x-8=4 | | 18+25=5x-2,x | | 17/13=v/9 | | 137+102+x=90 | | -5a+4a=28 | | 5x+16+9x-32=180 | | 5v-4+2(4v+5)=-3(v+2) | | 9x+4-4(-2x-1)=2(x-2) | | 3/4n+13=4 | | -7/6=-1/3+h= | | (1/4)^x=-1024 | | 4^x=-1024 | | 2/5n-6=-4 | | -3(w-1)=3w-45 | | 5v-4+2(4v+5=-3(v+2) | | 10b+-7-3b=6=24 | | n/7-3=-2 | | 1/3x^2=19 | | -2/3=-2/3u-1/2= | | 1/3x^2-19=0 | | 2.92x+9=5.2x-2.4 | | 4(x-1)=6x+4-4(-4x-1) | | 98.2x=33 |